2021
DOI: 10.1007/s40744-021-00326-8
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Risk of Immunoglobin G4-Related Disease: Evidence from a Large Cohort Multicenter Retrospective Study

Abstract: Introduction: The aim of this work was to evaluate the prevalence of malignancies in a multicenter cohort of Chinese patients with immunoglobulin G4-related disease (IgG4-RD) and to identify the related risk factors of malignancy in IgG4-RD patients. Methods: We retrospectively analyzed 602 IgG4-RD patients who were recruited in five medical centers from 2009 to 2020. Standardized prevalence ratios (SPRs) against the general Chinese population were calculated along with 95% confidence intervals (CIs). We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Herein,wefoundthatover90%ofpatientswithIgG4-RDhad at least one comorbidity, with the most prevalent being diabetes mellitus,hypertension,andatopy.Ourstudyshowedahigherprevalenceofdiabetes(47%)comparedwithpreviouslyreportedfigures (16.4%-39%). [6][7][8] We observed a higher prevalence of type 2 and type 3c diabetes in group 4, followed by group 1, which are the phenotypes in which pancreatic involvement is more prevalent. 3 Conversely, another study found diabetes to be more common in groups 1 and 4, despite higher cumulative doses of glucocorti-coidsingroup3.…”
Section: O R R E S P O N D E N C Ementioning
confidence: 58%
“…Herein,wefoundthatover90%ofpatientswithIgG4-RDhad at least one comorbidity, with the most prevalent being diabetes mellitus,hypertension,andatopy.Ourstudyshowedahigherprevalenceofdiabetes(47%)comparedwithpreviouslyreportedfigures (16.4%-39%). [6][7][8] We observed a higher prevalence of type 2 and type 3c diabetes in group 4, followed by group 1, which are the phenotypes in which pancreatic involvement is more prevalent. 3 Conversely, another study found diabetes to be more common in groups 1 and 4, despite higher cumulative doses of glucocorti-coidsingroup3.…”
Section: O R R E S P O N D E N C Ementioning
confidence: 58%
“…IgG4-related disease can create an immunological context that may impair the tumoral immunosurveillance and promote the pancreatic carcinogenesis [ 13 ]. Autoimmune pancreatitis was identifed as a potential risk factor for IgG4 related patients having malignancy [ 3 ]. Although autoimmune pancreatitis was not found in this patient, due to the potential for malignancy, physicians should be alert to this possibility during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-related disease is immune-mediated chronic inflammation that is diagnosed by clinicopathological presentations of enlarged organs, elevation of serum concentrations of IgG4 and pathological findings such as a typical dense lymphoplasmacytic infiltration enriched in IgG4-positive plasma cells, storiform fibrosis, and obliterative phlebitis [ 1 , 2 ]. Pancreas, kidney, and retroperitoneum are often affected [ 3 ]. However, there are few reports of IgG4-related disease involving the stomach.This article analysed a patient with IgG4-related disease who had a “stomach tumor” as the initial manifestation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, IgG4-RD is a fibrous-inflammatory process that often involves multiple organs, either synchronously or metachronously, including cervical lymph nodes, lung, liver, bile duct, gastrointestinal tract, central nervous system, thyroid, pancreas, kidney, prostate, arteries, lymph nodes, skin, breast, lacrimal glands and salivary gland [ 5 ]. Although organ distribution varies among studies, the pancreas, bile ducts, and salivary glands are the most frequently involved organs [ 2 , 6 ]. However, malignant tumors related to IgG4-RD proposed in the study were only confined to four diseases (pancreatic cancer, lymphoma, gastric cancer, and lung cancer).…”
Section: Main Textmentioning
confidence: 99%